2014
DOI: 10.1111/exd.12499
|View full text |Cite
|
Sign up to set email alerts
|

Skin disruption is associated with indomethacin‐induced small intestinal injury in mice

Abstract: One mechanism by which non-steroidal anti-inflammatory drugs (NSAIDs) cause intestinal injury is by inducing matrix metalloproteinases (MMPs) that degrade and remodel the extracellular matrix. In addition to the intestinal mucosa, MMPs are expressed in the skin and can be activated by mast cell-secreted tryptase. We therefore investigated whether intestinal injury resulting from treatment with the NSAID indomethacin induced MMPs in the skin of mice and caused an associated disruption of skin function. Hairless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…6,7) In a previous study, we have also reported that impaired skin barrier function was caused by mast cell degranulation in a mouse intestinal injury model. 2) In the present study, we confirmed that mast cells were present in the skin using toluidine blue staining, although no significant difference was observed between the mice that were treated with AOM+DSS and the control mice (data not shown). Therefore, it is necessary to clarify which causative molecular marker induces skin disruption in further studies.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…6,7) In a previous study, we have also reported that impaired skin barrier function was caused by mast cell degranulation in a mouse intestinal injury model. 2) In the present study, we confirmed that mast cells were present in the skin using toluidine blue staining, although no significant difference was observed between the mice that were treated with AOM+DSS and the control mice (data not shown). Therefore, it is necessary to clarify which causative molecular marker induces skin disruption in further studies.…”
Section: Discussionsupporting
confidence: 67%
“…2) Based on this finding, we postulated that other intestinal diseases might also influence skin barrier function, as there appears to be a close relationship between the skin and intestine. For example, inflammatory bowel disease involves several cutaneous manifestations, such as erythema nodosum and pyoderma gangrenosum.…”
mentioning
confidence: 93%
“…TEWL and the skin hydration levels of the dorsal skin were respectively measured using a Tewameter® TM300 and Corneometer® CM825 (Courage+Khazaka Electronic GmbH, Cologne, Germany) on days zero, seven, 14, and 21, according to previously described methods7.…”
Section: Methodsmentioning
confidence: 99%
“…One of the major intestinal tract diseases is inflammatory bowel disease (IBD), which occasionally complicates skin disorders as extraintestinal manifestations6. Additionally, the skin barrier function was impaired via mast cells in a small intestine-injured mouse model7. Further, in mice with colitis or colon cancer, the impaired skin barrier function occurred with destruction of type I collagen89.…”
Section: Introductionmentioning
confidence: 99%
“…We described the details of the staining method in our previous report [18]. Briefly, the specimens were incubated overnight at 4˚C with one of the following primary …”
Section: Preparation and Staining Of The Skin And Colonmentioning
confidence: 99%